PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN - Cahya Ayu Mulia Putri Rasyid; Eni Indriani; Robith Hudaya (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
The firm's value is important for the company because it affects its survival in the future. Many factors can affect firm value, such as disclosure and management of the capital structure. Disclosure is made to provide information to the public about the company, one of which is the disclosure of Corporate Social Responsibility (CSR) as a form of responsibility in terms of economic, environmental and social aspects. Capital structure management is carried out to achieve a balance between liabilities and equity to maximize the firm's value. This study examines the effect (CSR) and capital structure on firm value with firm size and profitability as moderators. The test was carried out on mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. This research is quantitative associative research with multiple linear regression and moderated linear regression with CSR and capital structure as independent variables and firm value as the dependent variable while the moderating variables are firm size and profitability. This study indicates that CSR has no effect on firm value, capital structure has a significant effect on firm value. Firm size and profitability cannot be a moderator of the influence of CSR and capital structure on firm value. This research implies that CSR disclosure has not been considered in making investment decisions and a large debt composition can reduce firm value.